2011
DOI: 10.1016/j.gca.2011.03.008
|View full text |Cite
|
Sign up to set email alerts
|

Determining individual mineral contributions to U(VI) adsorption in a contaminated aquifer sediment: A fluorescence spectroscopy study

Abstract: The adsorption and speciation of U(VI) was investigated on contaminated, fine grained sediment materials from the Hanford 300 area (SPP1 GWF) in simulated groundwater using cryogenic laser-induced U(VI) fluorescence spectroscopy combined with chemometric analysis. A series of reference minerals (montmorillonite, illite, Michigan chlorite, North Carolina chlorite, California clinochlore, quartz and synthetic 6-line ferrihydrite) was used for comparison that represents the mineralogical constituents of SPP1 GWF.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 84 publications
4
41
1
Order By: Relevance
“…Quartz and plagioclase feldspar (compositions ranging from albite to Na‐anorthite) were the major (>25%) constituents, with moderate (5%–25%) amounts of pyroxene (augite, diopside, and/or pigeonite), and minor (<5%) quantities of illite, kaolinite, and smectite. Detailed analysis of clay mineralogy on the <2 µm fraction was not undertaken but has been reported to include smectite, muscovite, vermiculite, and chlorite [ Qafoku et al ., ; Wang et al ., ]. Extractable iron and manganese (determined by CBD) increased by a factor of three from the largest to smallest size fraction (Table ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Quartz and plagioclase feldspar (compositions ranging from albite to Na‐anorthite) were the major (>25%) constituents, with moderate (5%–25%) amounts of pyroxene (augite, diopside, and/or pigeonite), and minor (<5%) quantities of illite, kaolinite, and smectite. Detailed analysis of clay mineralogy on the <2 µm fraction was not undertaken but has been reported to include smectite, muscovite, vermiculite, and chlorite [ Qafoku et al ., ; Wang et al ., ]. Extractable iron and manganese (determined by CBD) increased by a factor of three from the largest to smallest size fraction (Table ).…”
Section: Resultsmentioning
confidence: 99%
“…Extractable iron and manganese (determined by CBD) increased by a factor of three from the largest to smallest size fraction (Table ). Although present in low concentrations, phyllosilicates, as well as iron and manganese oxides, are likely adsorption sites for contaminant uranium [ Catalano et al ., ; Singer et al ., ; Stubbs et al ., ; Wang et al ., ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The spacing (Δ) between E and the first line of this series, S 1 , results in values for ν s in the ground state as follows: ν s = ∼870 cm −1 for the UO 2 2+ aquo ion 47,48 and 700 cm −1 < ν s < 800 cm −1 for uranium minerals (silicates, carbonates) and UO 2 2+ sorbed species. 26 in an ill-defined coordination environment (e.g. an amorphous matrix) are shown.…”
Section: Sample Preparationmentioning
confidence: 99%
“…15 These studies revealed (1) ions occupy sites in amorphous host matrices or at the surface of solids. 15,21,26,27 In both cases the local coordination environment of the luminescing species is ill-defined resulting in a significant variation of the energies of states of the sorbed UO 2 2+ ions. Although the electronic transition line for each single sorbed UO 2 2+ ion may be sharp, the position of the electronic transition line and the spacings between the vibronic lines will vary among non-equivalent sorbed UO 2 2+ ions, which results in inhomogeneously broadened overall electronic and vibronic transition bands composed of all the sharp lines of each single sorbed UO 2 2+ ion.…”
Section: Introductionmentioning
confidence: 99%